Comparative Efficiency of Genetically Dissimilar and Heat Stable live Newcastle Disease Vaccines against Velogenic NDV-Genotype VII - Madbouly, Yahia M.; Shakal, Mohamed; Aly, Eman H.; Hussein, Ashraf; Eid, Amal A.M. (Journal of Advanced Veterinary Research, 2024)
Newcastle disease virus (NDV) is accountable for causing one of the most contagious avian diseases in poultry, resulting in substantial financial losses worldwide. Both genotype I and II vaccines are commonly used for live NDV vaccination, particularly in broiler flocks. Recent years have witnessed a significant surge in the number of Newcastle disease outbreaks in Egyptian poultry broiler flocks, demonstrating the evolving nature of NDV infections and raising concerns regarding the effectiveness of existing NDV vaccination programs. In our study, a total of 200 one-day-old commercial chicks were divided into six groups, including unvaccinated group and five vaccinated groups. To assess the immunogenicity and protective efficacy of commonly used NDV vaccines against the prevalent Velogenic Viscerotropic Newcastle Disease Virus (vvNDV), The birds were administered live vaccines LaSota (Genotype II) and I2 (Genotype I) either as a single booster or a double booster after the initial priming with the HB1 vaccine. The comparative protective efficiency of all vaccine regimens assessment was based on clinical evaluation, observation of survival rates, and examination of viral shedding following vvNDV challenge. We also, evaluated the immune response to live vaccination by weekly monitoring of IgG specific antibodiesâ€™ levels in test sera. Â Our findings validated that the use of multiple live NDV vaccines can offer protection against the clinical symptoms of velogenic NDV, enhance protective immunity, and reduce the virus shedding after a challenge. The inclusion of heat stable I2 vaccine could be precious in the view of earth heating and weather change.